2018
DOI: 10.1016/j.jval.2017.08.3017
|View full text |Cite
|
Sign up to set email alerts
|

The CDI-DaySyms: Content Development of a New Patient-Reported Outcome Questionnaire for Symptoms of Clostridium difficile Infection

Abstract: The CDI-DaySyms captures symptoms relevant to patients undergoing CDI, demonstrating initial content validity. Final content and psychometric validity are being evaluated in a substudy comprising patients from two ongoing international clinical trials (ClinicalTrials.gov identifiers NCT01987895 and NCT01983683).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Across the 21 studies, humanistic CDI burden was assessed using four generic and two CDI disease-specific PRO measures designed for use in clinical trials. The generic HRQoL measures were EuroQol EQ-5D-3L (index and visual analogue scale [EQ VAS]) [ 25 , 26 , 30 , 37 ], 36-Item Short Form Health Survey (SF-36)/RAND-36 [ 22 , 29 , 38 40 ], Short Form 6-Dimension (SF-6D) [ 29 ], and National Health Institute’s Patient-Reported Outcomes Measurement Information System—Global Health (PROMIS-GH) [ 25 , 27 , 28 , 41 ]. The CDI disease-specific PROs included the C. difficile Health-Related Quality-of-Life Questionnaire (Cdiff32) [ 16 , 22 , 25 ] and the Clostridium difficile Infection–Daily Symptoms (CDI-DaySyms) [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Across the 21 studies, humanistic CDI burden was assessed using four generic and two CDI disease-specific PRO measures designed for use in clinical trials. The generic HRQoL measures were EuroQol EQ-5D-3L (index and visual analogue scale [EQ VAS]) [ 25 , 26 , 30 , 37 ], 36-Item Short Form Health Survey (SF-36)/RAND-36 [ 22 , 29 , 38 40 ], Short Form 6-Dimension (SF-6D) [ 29 ], and National Health Institute’s Patient-Reported Outcomes Measurement Information System—Global Health (PROMIS-GH) [ 25 , 27 , 28 , 41 ]. The CDI disease-specific PROs included the C. difficile Health-Related Quality-of-Life Questionnaire (Cdiff32) [ 16 , 22 , 25 ] and the Clostridium difficile Infection–Daily Symptoms (CDI-DaySyms) [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Current CDI and prior CDI missed more work and greater impairment while working and more activity impairment than never having CDI. Current CDI and prior CDI had significantly greater percentage of work missed, degree of impairment while working, degree of overall work impairment, and degree of activity impairment due to health than never CDI Kleinman et al [ 28 ] 2018 34 USA, Switzerland, Sweden CDI-DaySyms, PROMIS-GH item Patients with active CDI (pCDI or rCDI) Development of the CDI-DaySyms: 13-item, CDI-specific PRO designed to measure symptoms relevant to the general CDI population Kao et al [ 40 ] 2017 116 Canada SF-36 Survey developed to assess patient perceptions of FMT treatment Adults (18–90 years of age) with rCDI at 3 academic medical centers FMT via oral capsule vs colonoscopy FMT administered orally was not inferior to colonoscopy in preventing rCDI at 12 weeks. Prevention of rCDI after a single FMT treatment was 96.2% in both groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CDI-DaySyms™ is the first daily symptom diary measuring the broad range of CDI symptoms, which patients in a prior study reported as relevant and meaningful [18]. The development and validation of the questionnaire were rigorously completed in accordance with the FDA’s PRO Guidance for Industry [11].…”
Section: Discussionmentioning
confidence: 99%
“…In response to the lack of an adequate disease-specific daily diary (PRO) covering relevant patient-reported symptoms, the CDI-Daily Symptoms (CDI-DaySyms™) was developed. It measures the broad range of local and systemic CDI symptoms that patients report as meaningful [18].…”
Section: Introductionmentioning
confidence: 99%